Current status of liver transplantation for non‐B non‐C liver cirrhosis and hepatocellular carcinoma. Issue 1 (23rd August 2022) - Nishio, Takahiro; Ito, Takashi; Hata, Koichiro; Taura, Kojiro; Hatano, Etsuro
Abstract: Recently, non‐B non‐C chronic liver diseases, including alcoholic liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH), have markedly increased worldwide. Liver transplantation (LT) is an effective curative therapy for hepatocellular carcinoma (HCC) as well as decompensated liver cirrhosis. In Japan, where the source of liver grafts is strongly dependent on living donors, efforts have been made to unify the indications for eligibility of HCC patients for LT, leading to the development of 5‐5‐500 criteria. Along with the expansion of eligibility for LT, the current changing trends in underlying liver diseases of LT recipients, which are related to the rising tide of non‐B non‐C cirrhosis and HCC, are highlighting the importance of peri‐transplant management of patients with various comorbidities. The post‐LT prognosis of patients with ALD is significantly affected by de novo malignancies and metabolic syndrome‐related complications as well as posttransplant alcohol relapse. NAFLD/NASH patients often suffer from obesity, type 2 diabetes mellitus, and other metabolic syndrome‐related disorders, and nonneoplastic factors such as cardiovascular events and recurrence of NAFLD/NASH have a significant impact on post‐LT outcomes. Patient management in the peri‐transplant period as well as risk assessment for LT are key to improving post‐LT outcomes in the era of a growing number of cases of LT for non‐B non‐C liver diseases. Abstract : Recently, the cases of LT for non‐B non‐C cirrhosis and HCC have been increasing in Japan as well as worldwide. Perioperative management of non‐B non‐C liver disease is problematic due to various risk factors, including alcohol consumption and metabolic syndrome‐related risks, such as obesity and diabetes mellitus. This article aims to review the current status and issues of LT focusing on non‐B non‐C liver diseases, including HCC." cd_value_code="text